Estimating Nursing Staff of Tehran Hospitals by WHO and Levine Models - Alireza Namazi; Omid Khosravizadeh; Marziye Sharifi; Hasan Barkati; Samira Alirezaei; Amir Omrani (Iran University of Medical Sciences, 2016)
Background: Human resources, especially medical staff is one of the main components of health care system and organizational development. The purpose of this study was to estimate the required nurses for hospitals affiliated to Tehran University of Medical Sciences based on the models of the World Health Organization and Levine. Methods: This study was cross-sectional and descriptive. Seven hospitals affiliated to Tehran University of Medical Sciences were selected as research sample. After collecting data of the number and distribution of the nurses, the data were entered into Excel software. Then, according to the WHO and Levine formula, estimated numbers of hospital nurses were compared with the current situation. Results: According to the models, the number of nurses in all hospitals was different with standard values. According to WHO model, the correlation was negative and most hospitals but Amir Alam, Baharloo, and Farabi hospitals had insufficient number of nurses. Also, according to Levine model, all hospitals except Bahrami and Amir Alam hospitals had insufficient number of nurses. Conclusion: According to the World Health Organization and Levine model, the number of nurses in the studied hospitals was inadequate. This imbalance requires proper planning and standards to rectify the shortage of manpower, especially nurses in studied hospitals.